Limitations and benefits of MAX phases in electroanalysis - Tesař, Jan (2022)
MAX phases are a group of layered 2D materials made of early transition metal, A-group element (e.g., Al, Sn or Si), and C or N. These nanolaminated carbides and nitrides combine many attractive characteristics of metals and ceramics such as excellent electric and thermal conductivity and high chemical resistance. Although MAX phases have shown promising electrochemical results in the field of energy conversion, their use for electroanalytical approaches is nowadays an unexplored field. Herein, the potential use of MAX phases for electroanalytical approaches has been investigated. For this aim, seven different MAX phases (Cr2AlC, Mo2AlC, Ta2AlC, Ti2AlN, Ti2SnC, Ti3AlC2, Ti3SiC2, and V2AlC) have been drop-casted upon a conventional glassy-carbon electrode and tested at different pH media, also providing their potential towards the determination of different analytes. Overall, our findings elucidate the limitations and benefits of using MAX phases for electroanalysis, demonstrating that a proper combination of both MAX phases and electrolyte media is a must to direct efficient performances as electrode for electroanalysis. Accordingly, this work provides new knowledge about the electrochemical behaviour of MAX phases and their potential in the field of electronic devices.